DREADDs in Epilepsy Research: Network-Based Review - Mueller, John-Sebastian; Tescarollo, Fabio Cesar; Sun, Hai (Frontiers in Molecular Neuroscience, 2022)
Epilepsy can be interpreted as altered brain rhythms from overexcitation or insufficient inhibition. Chemogenetic tools have revolutionized neuroscience research because they allow “on demand” excitation or inhibition of neurons with high cellular specificity. Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) are the most frequently used chemogenetic techniques in epilepsy research. These engineered muscarinic receptors allow researchers to excite or inhibit targeted neurons with exogenous ligands. As a result, DREADDs have been applied to investigate the underlying cellular and network mechanisms of epilepsy. Here, we review the existing literature that has applied DREADDs to understand the pathophysiology of epilepsy. The aim of this review is to provide a general introduction to DREADDs with a focus on summarizing the current main findings in experimental epilepsy research using these techniques. Furthermore, we explore how DREADDs may be applied therapeutically as highly innovative treatments for epilepsy.